A Congenital anomalies and early neonatal mortality: A tertiary hospital study. - S. Talab , Hossam; Kamal, Ahmed; Z. Naama, Khalid (Journal of the Faculty of Medicine Baghdad, 2022)
Background: The prevalence of congenital anomalies at birth is underestimated in developing countries due to the unavailability of perinatal diagnostic tests or accurate medical records.  The prevalence of congenital defects may help to establish a baseline, track changes over time, and uncover etiological clues.Objectives: This study aims to evaluate the prevalence and types of major congenital anomalies in one of the main referral tertiary centers in Baghdad, highlighting the parent and neonatal characteristics and assessing the mortality rate in this group of patients.Patients and Methods: A prospective cohort study was conducted in Baghdad Teaching Hospital during the period between May 2017 and May 2018. Total deliveries were 6553, all live neonates with congenital anomalies were included regardless of their gestational age or birth weight. The patient's hospital notes were reviewed for the patient's characteristics, parentage, maternal chronic disease, and drug history, and other study parameters. The early neonatal outcome was assessed within 7 days of the delivery.Results: The prevalence of congenital malformations was 21.5 per 1000 birth with the highest frequent anomaly affecting the nervous system (41.1%) followed by multiple syndromic malformations (12.8%) and digestive system (11.3%). The mean maternal age was 27.8 (±7.8) ranging from 14-47. The rate of diseased mothers was 18.4%, only half of them were on regular medications. Out of a total of 399 early neonatal death during the study period, death due to congenital malformations constituted 19.8%.  Congenitally deformed patients died at a rate of 56%, which was significantly associated with gestational age and neonatal birth weight.Conclusion: The prevalence of congenital abnormalities has increased in the same hospital over the last decade. Mortality rate of these patients is high and associated with gestational age and birth weight. It is critical to test for congenital malformations early in pregnancy, particularly for high-risk parents with advanced age, consanguinity, and history of congenital anomalies.